Stability Analysis Of Magnetohydrodynamic Flow And Heat Transfer Over A Moving Flat Plate In Ferrofluids With Slip Effects - Ramli, Norshafira (2018)
A study of the stability analysis on the boundary layer flow has become a great interest in the field of fluid dynamics. This analysis is essential because it helps to identify which solution is stable if there exists non-unique solutions in the computation. In this thesis, the stability analysis is applied on the problems of the steady, two-dimensional, laminar, magnetohydrodynamic (MHD) flow and heat transfer over a moving flat plate in ferrofluids with suction and slip boundary conditions. It aims attention on the problem of forced and mixed convection immersed in an incompressible fluid. The three problems considered are; (1) MHD forced convection flow over a moving flat plate in ferrofluids with suction and second-order slip effects; (2) MHD mixed convection flow over a moving flat plate in ferrofluids with suction and slip effects; and (3) MHD mixed convection flow over a moving flat plate in ferrofluids with thermal radiation, suction and second-order slip effects. In order to solve these problems, the dimensional partial differential equations that governed the boundary layer flows are first transformed into non-dimensional equations by using appropriate dimensionless variables. These equations are then reconstructed into the form of nonlinear ordinary differential equations by applying the similarity transformation. The resulting system is solved numerically using the shooting method which is done with the aid of shootlib function in Maple software. This method is associated with the Runge-Kutta fourth order method together with Newton-Raphson as a correction scheme.